Examining the (Dis)Agreement between Etiology and Consequences of Adults' and Youths' Perceptions of Collective Efficacy in Boston. (November 2019) - Tucker, Riley; Zimmerman, Gregory M.; Stowell, Jacob I.; Jones, David Squier
Objectives: To examine the extent to which adults' and youths' perceptions of collective efficacy align, the shared and unique correlates of adults' and youths' perceptions, and the effects of adults' and youths' perceptions on youths' violence. Method: Descriptive analysis, hierarchical linear modeling, and spatial analysis analyze 1, 636 youths from the 2008 Boston Youth Survey and 1, 677 adults distributed across 85 neighborhoods from the 2008 Boston Neighborhood Study. Results: Descriptive analysis indicates that Boston adults' and youths' perceptions are largely divergent. Spatial analysis indicates that there is not clustering of either adults' or youths' perceptions across Boston neighborhoods. Multilevel models indicate that adults' and youths' perceptions exhibit divergent etiology: Adults' perceptions align closely with neighborhood collective efficacy and with their own neighborhood perceptions, while youths' perceptions are largely a function of individual differences (race and age) and sociobehavioral factors (social support and educational expectations). Youths' perceptions of collective efficacy, rather than aggregated adults' perceptions of collective efficacy, are inversely associated with youths' violence. Conclusions: Adults' and youths' perceptions of collective efficacy represent distinct constructs. Research should focus on the divergent processes through which adults' and youths' perceptions are generated and the differential effects of adults' and youths' perceptions on youths' behaviors.